2021
DOI: 10.1200/jco.20.03697
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Study on Dose Escalation in Definitive Chemoradiation for Patients With Locally Advanced Esophageal Cancer (ARTDECO Study)

Abstract: PURPOSE To analyze the effect of radiation dose escalation to the primary tumor on local tumor control in definitive chemoradiation (dCRT) for patients with esophageal cancer. PATIENTS AND METHODS Patients with medically inoperable and/or irresectable esophageal carcinoma, referred for dCRT, were randomly assigned between a standard dose (SD) of 50.4 Gy/1.8 Gy for 5.5 weeks to the tumor and regional lymph nodes and a high dose (HD) up to a total dose of 61.6 Gy to the primary tumor. Chemotherapy consisted of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
128
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(141 citation statements)
references
References 18 publications
1
128
1
11
Order By: Relevance
“…As the phase III ARTDECO study showed that dose escalation up to 61.6 Gy did not improve outcomes in patients with esophageal cancer, including patients with ESCC. 24 Currently, clinical trials are underway to explore the addition of PD-1 inhibitors and/or TGFβ to definitive chemoradiotherapy and will hopefully improve outcomes for patients with ESCC who are eligible for definitive chemoradiotherapy. 25,26 The phase III CheckMate 648 trial reported a survival time of 10.7 months for patients receiving chemotherapy alone, and an increased survival of 12.8 and 13.2 months for patients receiving nivolumab plus chemotherapy and nivolumab plus ipilimumab, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the phase III ARTDECO study showed that dose escalation up to 61.6 Gy did not improve outcomes in patients with esophageal cancer, including patients with ESCC. 24 Currently, clinical trials are underway to explore the addition of PD-1 inhibitors and/or TGFβ to definitive chemoradiotherapy and will hopefully improve outcomes for patients with ESCC who are eligible for definitive chemoradiotherapy. 25,26 The phase III CheckMate 648 trial reported a survival time of 10.7 months for patients receiving chemotherapy alone, and an increased survival of 12.8 and 13.2 months for patients receiving nivolumab plus chemotherapy and nivolumab plus ipilimumab, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To improve outcomes after definitive chemoradiotherapy, radiation dose escalation was considered an option until recently. As the phase III ARTDECO study showed that dose escalation up to 61.6 Gy did not improve outcomes in patients with esophageal cancer, including patients with ESCC 24 . Currently, clinical trials are underway to explore the addition of PD‐1 inhibitors and/or TGF‐β to definitive chemoradiotherapy and will hopefully improve outcomes for patients with ESCC who are eligible for definitive chemoradiotherapy 25,26 …”
Section: Discussionmentioning
confidence: 99%
“…The use of F-IGRT has many potential benefits over S-IGRT, including facilitating a higher dose focused on the tumor with a lower dose delivered to cover the submucosal spread, and more accurate treatment delivery (matching to the tumor rather than surrounding bony structures)[ 17 , 28 ]. There are conflicting data regarding the efficacy of increased radiation dose in treating oesophageal cancer[ 29 , 30 ]. While some retrospective studies demonstrated a dose-response, recent randomized control trials failed to find a difference in outcomes[ 31 - 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In der hier kommentierten, randomisierten Phase-III-Studie ARTDECO wurde nach einer medianen Nachbeobachtungszeit von 50 Monaten der primäre Endpunkt des lokal progressionsfreien Überlebens (LPFS) nach einer Dosiseskalation der Strahlentherapie von 50,4 Gy auf 61,6 Gy auf den Primärtumor nicht signifikant verbessert [ 4 ]. Einige Aspekte der Studie sind deshalb hier erwähnenswert.…”
Section: Kommentarunclassified